JADID LITERATURE: HISTORICAL FORMATION, CORE IDEAS AND LITERARY CHARACTERISTICS (Web of Teachers: Inderscience Research, 2025)
The article explores the origins, development stages, and societal role of Jadid literature. The key representatives of the Jadid movement, their creative legacy, and literary ideas are analyzed. The study highlights the role of new-method schools and the press in fostering national identity and advancing education. Soviet-era repressions and the contemporary significance of the Jadid heritage are also examined. The social and educational functions of Jadid literature and its modern interpretation are discussed